KEEFEKTIFAN MEDIA BUILD GEOMETRY DALAM MENINGKATKAN KEMAMPUAN BERNALAR KRITIS WARGA BELAJAR PENDIDIKAN KESETARAAN PAKET A - Ayu Sri Rejeki; Iin Purnamasari; Agus Sutono (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purposes of this study were to: (1) Test the effectiveness of build geometry learning media on the critical reasoning abilities of citizens learning Equivalence Education Package A PKBM Pelita Mandiri, (2) Measuring differences in critical reasoning abilities of citizens learning Equality Education Package A PKBM Pelita Mandiri before and after using geometry build learning media.The research method used is quantitative experiment. This research was conducted on learning mathematics and the subjects were residents studying Equality Education Package A class VI PKBM Pelita Mandiri Semarang, totaling 41 children. Data collection techniques using observation, tests, questionnaires and documentation. The type of data analysis used in this study uses descriptive analysis, normality test, t test and N Gain Score test with the help of the SPSS computer program and Microsoft Excel 2019.The results of the study showed that: (1) the effectiveness of build geometry media to improve critical thinking skills was obtained from the posttest results in the experimental class and control class through the N Gain Score test for the experimental class higher than the control class with an average of 68.99 (2) the improvement of critical reasoning skills through media build geometry was obtained from the results of the posttest with the results of the t test which stated that the sig. (2-tailed) 0.00. Increase ≤ 0.05, which means there is an increase in critical thinking skills in the experimental class.